Pengaruh Komunikasi Positif dalam Keluarga dan Komunikasi Interpersonal Guru terhadap Perilaku Asertif Siswa - Ardianto . (Institut Agama Islam Negeri (IAIN) Manado, 2016)
This study aims to perform a significance test of (1) the positive communication within the family on students’ assertive behavior, (2) the teachers’ interpersonal communication on students’ assertive behavior, and (4) the positive family communication and teachers’ interpersonal communication simultaneously on students’ assertive behavior. This is a quantitative study using a survey questionnaire in data collection. This research is conducted at MAN Model Manado. The research population is all students of the 10th, 11th, and 12th grade, totaling 1406. The sample size of 87 students is selected by a simple random sampling. The results show that (1) while the level of the positive communication within the family, and of the students’ assertive behaviour perceived by the students is relatively low, the level of the teachers’ interpersonal communication is relatively high; (2) a positive communication within the family has a significant effect on students’ assertive behavior; (3) an interpersonal communication has a significant effect on students’ assertive behavior; and (4) a positive family communication and teachers’ interpersonal communication simultaneously have a significant effect on students’ assertive behavior.Keywords: Positive communications within family, teachers’ interpersonal communications, students’ assertive behaviors